2012
DOI: 10.1128/jcm.06595-11
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Three Assays for Detection of Chlamydia trachomatis and Neisseria gonorrhoeae in SurePath Pap Samples and the Role of Pre- and Postcytology Testing

Abstract: Chlamydia trachomatis andC hlamydia trachomatis and Neisseria gonorrhoeae infections are the most frequently reported bacterial sexually transmitted diseases in North America (1). Because of the high rates of asymptomatic infection, which may lead to upper genital tract complications such as pelvic pain, ectopic pregnancy, and infertility, control requires some form of screening to identify and treat infected patients and their partners (9). Specimens from cervical cancer screening programs are being considere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2013
2013
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…With clearance by the U.S. Food and Drug Administration and other regulatory agencies in Europe and elsewhere of several systems, automated molecular testing has become routine in clinical laboratory practice, ensuring diagnostic accuracy and improved result turnaround time (TAT). Studies have been published assessing clinical performances of molecular assays (2)(3)(4)(5)(6)(7)(8), and workflow and maintenance characteristics of automated instruments (9)(10)(11)(12)(13)(14)(15)(16). In addition to performance and instrumentreagent costs, hands-on time required for testing and maintenance, in-process interaction, and time to results and test capacity are key metrics that should be considered because they can influence efficiency and labor costs.…”
mentioning
confidence: 99%
“…With clearance by the U.S. Food and Drug Administration and other regulatory agencies in Europe and elsewhere of several systems, automated molecular testing has become routine in clinical laboratory practice, ensuring diagnostic accuracy and improved result turnaround time (TAT). Studies have been published assessing clinical performances of molecular assays (2)(3)(4)(5)(6)(7)(8), and workflow and maintenance characteristics of automated instruments (9)(10)(11)(12)(13)(14)(15)(16). In addition to performance and instrumentreagent costs, hands-on time required for testing and maintenance, in-process interaction, and time to results and test capacity are key metrics that should be considered because they can influence efficiency and labor costs.…”
mentioning
confidence: 99%
“…The similarity in the data may be related to our small sample size because discordances in data from larger data sets have previously been identified [10][11][12]18]. Indeed, an overall agreement of 98.5% between the results from the Abbott RealTime and Roche Cobas Amplicor assays in the diagnosis of CT on cervical swab samples was reported in 96.3% (26/27) of the positive results and in 100% (40/40) of the negative results [12].…”
Section: Discussionmentioning
confidence: 54%
“…3A), apart from analytical variance related to the Cervista assay, suggests that the risk for cross-contamination related to the Tigris DTS itself is also very minimal. Chernesky et al (18) reported Ͼ98% agreement of Aptima Combo 2 (Hologic/Gen-Probe) Chlamydia trachomatis results in precytology and postcytology fractions of 394 SurePath (BD Diagnostics-TriPath, Burlington, NC) collections. The data in our study not only were generated on the basis of a different microbe and an alternative liquid-based cytology medium but also were assessed with an automated platform for nucleic acid amplification testing and an automated means of cytology processing.…”
Section: Discussionmentioning
confidence: 99%